THE ROLE OF STRATEGIC CLARITY IN ACHIEVING SUSTAINABLE HUMAN RESOURCES ORIENTATION: ANALYTICAL STUDY OF A SAMPLE OF STAFF AT ZAHRA TEACHING HOSPITAL IN GOVERNORATE NAJAF AL-ASHRAF - Noor Sabah Jalil al-balagheeb; Ihsan Abdulmeer Azeez; Samaa Ali al_zubaidie (Scholars Digest Publishing, 2023)
The purpose/objective: of the study is to identify the role that strategic clarity plays in achieving sustainable human resources orientation. Theoretical framework: Given the importance of the health system and the keen desire to develop this system that suffers from extreme neglect, the study attempts to activate the sustainable orientation of human resources, which is the key element of the health sector's work by activating the role of strategic clarity. Methodology: Reliance on workers in the health sector(Zahra Educational Hospital in governorate Najaf Al-Ashraf) To be the sample study to determine the differences between them at the dimension level and research variables, It has been collected (97) Valid for statistical analysis / Through which statistical analysis of the main hypothesis and branching sub-hypotheses was carried out using the statistical program (spss) To determine whether there is an association and effect between the study variables. Results: The results demonstrated that strategic clarity plays a significant role in achieving the health system's goals of moving towards the sustainability of human resources through all outcomes associated with fundamental and sub-variables of research. Scientific and social implications of research: Through the findings of the research, it was found that there is an influential role for strategic clarity in activating the trend towards the sustainability of human resources within the health sector. However, this impact varied among the sub-dimensions of the research. Authenticity/Value: Recommends research to adopt strategic clarity As a consistent platform in the health sector, it plays a significant role in maintaining the sustainability of its human resources through the establishment of mechanisms and established criteria for strategic clarity.